THE CURRENT ROLE OF ENGLISH AS A GLOBAL LANGUAGE AND THE IMPORTANCE OF THIS LANGUAGE IN ECONOMIC, SOCIAL AND CULTURAL TERMS - Turdaliyeva Shahnoza O'ktamovna (American Journals, 2023)
In today's rapidly developing era, the importance and role of the English language is increasing more and more. It is widely used not only in English-speaking developed countries, but also in small countries that are developing and preparing for development in every corner of the world. English is spreading widely not only as a scientific language, but also as an industrial language, a medical language, a technological language, and a business and commercial language. In this article, we have presented the proof of this more clearly and also briefly described the history of the English language.
Keywords: Anglophone, primary language, crucial, prevalent, conducting business, origin, communication, eminent.